Community nutrition for developing countries - Temple, Norman J.; Steyn, Nelia P. (Nelia Patricia) (Edmonton, AB : AU Press, University of Athabasca ; [South Africa] : UNISA Press, University of South Africa, 2016)
"Nutrition textbooks used by universities and colleges in developing countries have very often been written by scholars who live and work in North America or the United Kingdom. And while the research and information they present is sound, the nutrition-related health challenges with which developing countries must grapple differs considerably from those found in highly industrialized Western nations. The primary aim of Community Nutrition for Developing Countries is to address this issue. Written by both scholars and practitioners, the volume draws on their wealth of knowledge, experience, and understanding of nutrition in developing countries to provide nutrition professionals with the proper tools for the assessment and evaluation of nutritional status. Each chapter addresses a specific nutrition challenge currently faced by developing countries such as food security, food safety, disease prevention, maternal health, and effective nutrition policy. In addition, the volume serves as an invaluable resource for those developing and implementing nutrition education programmes. With an emphasis on nutritional education as a means to prevent disease and effectively manage health disorders, it is the hope of the nearly three dozen contributors to this work that it will enhance the health and wellbeing of low income populations throughout the world."--
The food and nutrition situation in developing countries -- Lifecycle nutrition -- The role of nutrition in the prevention and treatment of disease -- From food guides to nutrition education -- Key components of community-based nutrition programs -- Population nutrition and the role of the government -- Assessing nutrition status -- Food services and food safety -- A broader perspective.
Includes bibliographical references.
Online resource; title from PDF version (Library and Archives Canada Electronic Collection, viewed June 21, 2021)
eBooks on EBSCOhost
Keywords: Nutrition -- Developing countries; Nutritionally induced diseases -- Developing countries -- Prevention; Nutrition -- Evaluation; Diet in disease; Nutritional Status; Developing Countries; Deficiency Diseases -- prevention & control; Diet; Nutrition Assessment; Nutrition -- Pays en voie de développement.; Maladies d'origine nutritionnelle -- Pays en voie de développement -- Prévention.; Nutrition -- Évaluation.; Régimes alimentaires; BUSINESS & ECONOMICS -- Infrastructure; SOCIAL SCIENCE -- General; Nutrition -- Evaluation; Diet in disease; Nutrition; Nutritionally induced diseases -- Prevention; Developing countries; Voeding; Ontwikkelingslanden; nutritional status; prevantable disease; immunizations; AIDS; maternal health; poverty; Electronic books; Electronic books